Open Balkan initiative: Prospects for tourism development - Biljana Petrevska (UTMS Journal of Economics, 2022)
The paper discusses the prospects of the Open Balkan initiative for the tourism development of North Macedonia. It presents an overview of this political initiative established to improve regional economic collaboration in the Western Balkans. In 2022, North Macedonia, Serbia, and Albania signed a Memorandum of understanding on cooperation in the field of tourism in the Western Balkans to expand the tourism potential of a common tourism market. This study investigates the level of seasonality in terms of overnights of tourists from Serbia, and Albania between 2011-2019. Data for 2020 and 2021 are omitted due to COVID-19 pandemic break. By calculating standard indicators, the research revealed low seasonality and favorable precondition for creating sustainable regional tourism product based on cultural heritage, tradition, gastronomy, and other cultural similarities. The study further outlines the importance of establishing a single tourism market that will contribute to creating a new concept of integrated regional tourism.
Keywords: L83; Z32; Z38; 330; Open Balkan initiative; regional development; tourism market; seasonality